2016
DOI: 10.1007/s11427-016-5042-5
|View full text |Cite
|
Sign up to set email alerts
|

Small G Rac1 is involved in replication cycle of dengue serotype 2 virus in EAhy926 cells via the regulation of actin cytoskeleton

Abstract: Bleeding is a clinical characteristic of severe dengue and may be due to increased vascular permeability. However, the pathogenesis of severe dengue remains unclear. In this study, we showed that the Rac1-microfilament signal pathway was involved in the process of DENV serotype 2 (DENV2) infection in EAhy926 cells. DENV2 infection induced dynamic changes in actin organization, and treatment with Cytochalasin D or Jasplakinolide disrupted microfilament dynamics, reduced DENV2 entry, and inhibited DENV2 assembly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
0
13
0
2
Order By: Relevance
“…The cytoskeleton has been reported to function at several stages of the replication cycle for members of the Flaviviridae family. For DENV infection, entry into host cells depends on microfilament integrity 132,133 . Additionally, the formation of viral ROs causes substantial remodelling of the intracellular endomembrane system and concomitantly alters the cytoskeletal architecture.…”
Section: Cytoskeletonmentioning
confidence: 99%
“…The cytoskeleton has been reported to function at several stages of the replication cycle for members of the Flaviviridae family. For DENV infection, entry into host cells depends on microfilament integrity 132,133 . Additionally, the formation of viral ROs causes substantial remodelling of the intracellular endomembrane system and concomitantly alters the cytoskeletal architecture.…”
Section: Cytoskeletonmentioning
confidence: 99%
“…In EAhy926 cells, Rac1 has been reported to play an important role in the DENV serotype 2 (DENV2) life cycle by regulating actin reorganization. DENV2 infection induced dynamic changes in actin organization, and treatment with cytochalasin D or jasplakinolide disrupted actin dynamics, reduced DENV2 entry, and inhibited DENV2 assembly and maturation (Zhang et al 2016). Works in ECV304 cells showed that actin and Rac1 signaling are essential for DENV2 entry into and release from the host cell (Wang et al 2010).…”
Section: The Role Of Cytoskeleton In Denv-host Interactionmentioning
confidence: 99%
“…However, the underlying mechanisms of RAC1 activation in various types of cancer tend to be varied and complex (35). In our study, we further found that ectopic overexpression of the RAC1 short-3 0 UTR isoform in UCB cells dramatically increased protein expression of RAC1 by escaping from miRNA targeted repression and thus, largely up-regulating certain key targets, AKT and b-catenin-MMP9 pathways, which can potently stimulate cancer cell proliferation and invasion (36,37). These findings suggest that 3 0 UTR shortening of RAC1 in UCB is a critical mechanism to upregulate RAC1 expression and consequently promote UCBs tumorigenesis and/or progression.…”
Section: Discussionmentioning
confidence: 51%